2017
DOI: 10.17475/kastorman.288926
|View full text |Cite
|
Sign up to set email alerts
|

Female Fertility in Pinus sylvestris L var. compacta (TOSUN) Clonal Seed Orchard

Abstract: Aim of study: The intention of current study is to compile information on female fertility variation and estimate some parameters related to fertility in the seed orchard for 2015. Area of study: The seed orchard was established in April 2004 in Eflani of Karabuk, Turkey. Material and Methods: The seed orchard included 823 ramets of 26 clones at 5m x 5m. Five ramets per clone were chosen randomly and female strobili in 130 ramets were counted in June 2015. All of the female strobili over the entire crown were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Dioryctria Zeller (Lepidoptera: Pyralidae) species cause a significant damage to cones and seeds (Aslan, 2018;Bracalini et al, 2013;Leal-Sáenz et al, 2021). Damage caused to tree cones by Dioryctria spp.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Dioryctria Zeller (Lepidoptera: Pyralidae) species cause a significant damage to cones and seeds (Aslan, 2018;Bracalini et al, 2013;Leal-Sáenz et al, 2021). Damage caused to tree cones by Dioryctria spp.…”
Section: Resultsmentioning
confidence: 99%
“…Aytar (2001) reported that the size of damaged area by Dioryctria splendidella Herrich-Shaeffer reached 390.0 ha in 1997, 1707.0 ha in 2000, and 1704.0 ha in 2001 in P. brutia forests of Adana and Mersin Forest Regional Directorate. In addition, Aslan (2018) reported that the larvae of D. simplicella caused damage to P. sylvestris in Kastamonu in Turkey. In northern Arizona, Dioryctria auranticella Grote destroyed 38-81% of Pinus ponderosa Doug.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations